A resolução dos conflitos sociomorais e suas implicações na construção da autonomia moral dos alunos - Leonardi, Eleodora dos Santos (2008)
This summation refers to the investigation inserted in the Curriculum, Teaching and School Practices Research Line (PPGE/CE/UFSM). The objective was to understand the implications of the solution of sociomoral conflicts on the moral autonomy building of students. The methodology used, it was described as qualitative under a case study perspective. The subjects who participated in the research were two Beginner Years of Fundamental Teaching fourth grade teachers and their respective groups. The context in which the research took place was a state school that belongs to the public instruction net of the city of Santa Maria-RS, the school being located at periphery of the city. The data was gathered through semistructured interviews and classroom live observation. The analysis of that data was organized into three categories, according to its frequency and centralization, in a quest for understanding the study: the solution of the sociomoral conflicts, the sociomoral rules and environment and the limits to be trespassed: the possible autonomy. Those categories were explored having the concept of morality presented by Jean Piaget as axis. From the acquired data analysis, one can conclude that the means the teachers used for solving the sociomoral conflicts did not favour the sociomoral autonomy building of the students. Because their practices were ruled, mainly, by coercion relationships, based on unilateral respect. From this investigation, one can understand the importance of sociomoral conflicts solution learning to be conceived in the educational institutions curriculum as an useful knowledge which will grant a pedagogical practice aimed at the moral autonomy building of the students.